3440 Emergency Dispatch Research Workshop: Engaging a Forgotten Professional Population in Research. (27th March 2019) - Wheeler, Alissa L; Gardett, Isabel
Abstract : OBJECTIVES/SPECIFIC AIMS: Emergency (911) dispatchers are the first link in the chain of care for the estimated 240 million emergency calls made each year. Yet even as emergency medicine, public safety, and public health have seen increasing study, emergency dispatch has very seldom been included in that research. Part of the reason is that, while emergency medicine is connected with hospital physicians and public health with university departments, emergency dispatch is largely invisible, not represented in university programs, and staffed by professionals without research training–and often without higher education or academic degrees. The purpose of our Dispatch Research Workshop is to engage these professionals in guided research projects of their own design, with the ultimate aims of both engaging more emergency dispatchers in research and increasing the field's overall capacity to generate evidence-based practice. METHODS/STUDY POPULATION: The workshop is help in tandem with a national Emergency Dispatch conference. Participants are recruited through advertisements in professional journals and relevant social media sites. The workshop is co-led by members of a partnership between the nonprofit organizations the International Academies of Emergency Dispatch and the UCLA Prehospital Care Research Forum, along with the dispatch data aggregation company FirstWatch. The Workshop occurs over two eight-hour days, and participants generally have no research experience or background. By the end of the second day, groups have developed research questions and methods, begun to write IRB proposals, and created data collection and analysis plans. Throughout the remainder of the year, research mentors support the completion of the project, and completed projects are presented at the following year's conference and submitted (if desired) for publication. RESULTS/ANTICIPATED RESULTS: During the first two years of the workshop, 36 attendees participated (17 the first year and 19 the second). Three successful attendees of the first workshop helped lead the second as research mentors. Three research projects were completed from the first year; all three were presented as posters and are now being prepared for publication as manuscripts. Four projects have emerged from the second year's workshop. Assessments and one-on-one interviews with participants at the end of each workshop have led to continuous change and improvement in the delivery of the material, as well as the outline of a year's worth of support materials, which is currently in development. DISCUSSION/SIGNIFICANCE OF IMPACT: Developing a true evidence base for practice in emergency dispatch will serve all of our communities, and feedback from our participants (as well as significant existing research in practitioner-engaged research) indicates that those who participate in research have a better understanding of the value of evidence-based practice, are more likely to adopt it, and are more likely to raise questions and test theories in their own professional life. Also, providing these practitioners the opportunity to conduct and publish research raises their stature and the stature of their profession, helping it achieve its rightful place alongside other professions in public safety and health.